Modeling то safety of the responsible technological processes - Shilko, С.В.; Komnatny, Д.В. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The sources of risk caused by technological equipment failure under electromagnetic impulse, extra heating, wear and other factors are discussed. It’s shown that solution of risk minimization problem may be obtained on the base of modeling of stability of technological regime. For example, the probabilistic model of the electromagnetic impulse influence on technological regime is developed.